An Analysis of Tax Avoidance: The Impact of Financial Performance with the Tax Harmonization Law (UU HPP) As A Moderating Variable - Sholikhah, Siti Nur Amalis; Kusuma, Marhaendra; Kusumaningarti, Miladiah (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study aims to analyze the influence of financial performance proxied through Return on Assets (ROA), Debt to Equity Ratio (DER), and Firm Size on Tax Avoidance with the Law on Harmonization of Tax Regulations (UU HPP) as a moderation variable. This study uses a quantitative approach with a descriptive method. Population is a company listed on the Indonesia Stock Exchange (IDX) for the 2019–2024 period. Samples are determined through purposive sampling techniques. Data analysis was carried out using the Moderated Regression Analysis (MRA) test. The results showed that partially, ROA, DER and firm size did not have a significant effect. The HPP Law is also unable to moderate the relationship between financial performance and tax avoidance